Investigating MRI-Induced Anxiety: A Study of State and Trait Anxiety Levels Using the State-Trait Anxiety Inventory - Jha, Abinash; Yadav, Rajesh Prasad; Chandra, Avinash; Yadav, Shree Narayan (Annapurna Journal of Health Sciences, 2026)
Introduction: Magnetic Resonance Imaging (MRI) is a non-invasive imaging modality widely used in diagnostics, yet it can provoke significant anxiety that may compromise image quality and diagnostic accuracy.This study assessed MRI-induced anxiety and identified predictors of post-procedural anxiety using the State-Trait Anxiety Inventory (STAI). Methods: An observational study was conducted among 384 adult patients undergoing MRI at a tertiary care hospital. The STAI-Trait (STAI-T) was administered before the scan; the STAI-State (STAI-S) was completed before and immediately after MRI. Wilcoxon signed-rank tests, independent t-tests, and multiple linear regression analyses were used. Results:The mean trait anxiety score was 41.8 (SD+-8.7), with females scoring significantly higher than males (p = 0.0004). Although median STAI-S scores showed no statistically significant change (p = 0.5676), the proportion of patients with high anxiety (STAI-S ≥ 55) increased from 9.9% to 27.1% post-MRI. Female gender (β = 0.21, p < 0.01), first-time MRI experience (β = 0.18, p < 0.05), and elevated trait anxiety (β= 0.38, p < 0.001) were significant predictors, accounting for 38% of the variance inpost-MRI anxiety (Adjusted R² = 0.38). Conclusion: A substantial rise in high post-scan anxiety was observed, despite unchanged group-level averages. Routine psychological screening and targeted interventions are recommended for at-risk individuals.